Criminal Act of Drugs Abuse as Extraordinary Crime in Indonesia - Suaib, Hermanto; Subaidi, Joelman; Hatta, Muhammad; Rahman, Sufirman; Khoiri, Ahmad; Khoiri, Ahmad (International Journal of Psychosocial Rehabilitation, 2020)
Judging from the large negative impact of drug abuse on health, social, cultural, economic and political, this crime is categorized as an extraordinary crime. In the Commission III of the House of Representatives Working Meeting with the National Narcotics Agency (BNN) stated that narcotics crimes are extraordinary, organized and transnational crimes that lead to several other crimes such as terrorism, arms smuggling, human trafficking and other similar crimes. In the decision of the Constitutional Court No. 2 / PUU-V / 2007 and No. 3 / PUU-V / 2007, criminal acts of drugs are categorized as extraordinary crimes because they are particularly serious crimes that can negatively affect economic, cultural, and political foundations of society and cause a danger of incalculable gravity. Therefore, Law No. 35 of 2009 concerning Narcotics and Law No. 5 of 1997 concerning psychotropic determines that the weighting of sentences on drug dealers is similar to the capital punishment (death penalty).